2022
DOI: 10.1101/2022.03.31.486560
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EEG-representational geometries and psychometric distortions in approximate numerical judgment

Abstract: When judging the average value of sample stimuli (e.g., numbers) people tend to either over- or underweight extreme sample values, depending on task context. In a context of overweighting, recent work has shown that extreme sample values were overly represented also in neural signals, in terms of an anti-compressed geometry of number samples in multivariate electroencephalography (EEG) patterns. Here, we asked whether neural representational geometries may also reflect underweighting of extreme values (i.e., c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 73 publications
(143 reference statements)
0
3
0
Order By: Relevance
“…For completeness, we note that in addition to our main finding of adaptive distortions, participants' decisions also showed characteristics that were not encompassed by our model simulations: a "leakage" of sample information over time (i.e., a "recency" bias toward later presented samples), and an overall bias toward larger numbers (e.g., choices were more strongly driven by sample values "9" than "1," although the latter provided equally strong objective evidence). Both of these biases have been reported repeatedly in previous work (Anderson, 1964;Appelhoff et al, 2022aAppelhoff et al, ,2022bCheadle et al, 2014;Hubert-Wallander & Boynton, 2015;Luyckx et al, 2019;Spitzer et al, 2017;Summerfield & Tsetsos, 2015;Weiss & Anderson, 1969;Yashiro et al, 2020), but their precise origin and functional role remain unclear. These biases were not modulated in interpretable ways by our present experimental manipulations, leaving their further investigation to future work.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…For completeness, we note that in addition to our main finding of adaptive distortions, participants' decisions also showed characteristics that were not encompassed by our model simulations: a "leakage" of sample information over time (i.e., a "recency" bias toward later presented samples), and an overall bias toward larger numbers (e.g., choices were more strongly driven by sample values "9" than "1," although the latter provided equally strong objective evidence). Both of these biases have been reported repeatedly in previous work (Anderson, 1964;Appelhoff et al, 2022aAppelhoff et al, ,2022bCheadle et al, 2014;Hubert-Wallander & Boynton, 2015;Luyckx et al, 2019;Spitzer et al, 2017;Summerfield & Tsetsos, 2015;Weiss & Anderson, 1969;Yashiro et al, 2020), but their precise origin and functional role remain unclear. These biases were not modulated in interpretable ways by our present experimental manipulations, leaving their further investigation to future work.…”
Section: Discussionmentioning
confidence: 66%
“…Here, we showed that whether people subjectively compress or anticompress numerical values depends on whether they are asked to assess the average value of a single stream or to compare the values of two interleaved streams. Arguably, the latter task is cognitively more effortful, because evaluating a sample's decision value for the comparison requires more cognitive operations (see also Appelhoff et al, 2022b). The pattern of results matches the predictions of our simulations with a psychometric model, which showed that compression yields a performance benefit for noisy observers when tasks are within their processing limit, whereas anticompression improves performance in computationally demanding tasks (i.e., where evaluating a sample properly comes at the cost of missing the decision information in other samples).…”
Section: Discussionmentioning
confidence: 99%
“…EEG data were first pre-processed by following the standardized preprocessing offered by the PREP pipeline [13], [14]. The data were then filtered with a finite impulse response filter with a highpass frequency of 8 Hz and a lowpass frequency of 30 Hz as these frequencies contain most information related to MI [15].…”
Section: B Data Processingmentioning
confidence: 99%